(untitled) (Світ фінансів, 2017)
Смалюк Г. Ф., Булавська Г. О. Проблеми інноваційного розвитку економіки України. Розглянуто основні аспекти інноваційного розвитку економіки України. Досліджено причини відставання та запропоновано шляхи підвищення конкурентоспроможності нашої держави в світовій високотехнологічній економіці. Smalyuk G., Bulavska H. The problems of innovative development of economy of Ukraine. The basic aspects of innovative development of economy of Ukraine are considered. The reasons of lag are explored and the ways of increase competitiveness of the state in a world hitech economy are offered.